Regulatory policy in Latin America An analysis of the state of play - Querbach, Tobias (OECD Regulatory Policy Working Papers, 2017)
Regulation is a critical tool by which governments seek to foster economic growth and social well-being. Countries in Latin America are increasingly investing in processes and institutions that support regulatory quality. Based on the OECD Indicators of Regulatory Policy and Governance (iREG) for Latin America 2016, this paper explores the state of play of regulatory policy in seven countries in Latin America and identifies potential opportunities to improve. The annex includes individual profiles of each of the countries covered, highlighting key achievements and challenges. The analysis of the data shows that countries in the LAC region have taken steps to improve their regulatory governance framework but important gaps remain in most countries in terms of the implementation of key tools, such as consultation with stakeholders, Regulatory Impact Assessment (RIA) and ex post evaluation. Strengthening the institutional oversight of the regulatory process will be critical to ensure the consistent implementation of these tools in the future